2016
DOI: 10.1039/c5nj02400e
|View full text |Cite
|
Sign up to set email alerts
|

A simple one-pot Adams method route to conductive high surface area IrO2–TiO2 materials

Abstract: The Adams method is used to prepare IrO2–TiO2 materials, composed of nanoparticles, whose electrical conductivity follows percolation theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 38 publications
8
58
1
Order By: Relevance
“…Energy Mater. Catalyst layer conductivities of 3 to 7 S cm −1 , equilibrated at the different gas phase humidity, are observed that are comparable to literature values of 1 to 4 S cm −1 [56] for materials with same Ir content (IrO 2 /TiO 2 catalysts > 60 %mol). To decode this missing link between optimal PTL microstructure and high catalyst utilization, the conduction mechanism in anodic catalyst layers needs to be analyzed.…”
Section: Elucidating the Mechanistic Of The Mpl Effectsupporting
confidence: 87%
See 1 more Smart Citation
“…Energy Mater. Catalyst layer conductivities of 3 to 7 S cm −1 , equilibrated at the different gas phase humidity, are observed that are comparable to literature values of 1 to 4 S cm −1 [56] for materials with same Ir content (IrO 2 /TiO 2 catalysts > 60 %mol). To decode this missing link between optimal PTL microstructure and high catalyst utilization, the conduction mechanism in anodic catalyst layers needs to be analyzed.…”
Section: Elucidating the Mechanistic Of The Mpl Effectsupporting
confidence: 87%
“…[18] To better understand the effect of ionomer swelling on catalyst layer conductivity, the influence of ionomer weight fraction (3 to 18 %wt) at constant catalyst loading on electrical in-plane conductivity was analyzed ex situ during a humidification cycle (dry → 100 %rh → liquid water → dry), see Figure 5a. Catalyst layer conductivities of 3 to 7 S cm −1 , equilibrated at the different gas phase humidity, are observed that are comparable to literature values of 1 to 4 S cm −1 [56] for materials with same Ir content (IrO 2 /TiO 2 catalysts > 60 %mol). For ionomer contents up to 11 %wt, the conductivity differences are not significant and are within the standard deviation of the measurements.…”
Section: Elucidating the Mechanistic Of The Mpl Effectsupporting
confidence: 87%
“…Several authors attributed the improved conductivity to structural modifications of the Ti lattice . In contrast, percolation would rely on conductive oxide islands distributed throughout a matrix of non‐conductive TiO 2 . Only when a certain threshold of the content of conductive oxide is reached a sufficient number of conductive domains become connected and conductivity starts to increase.…”
Section: Resultsmentioning
confidence: 98%
“…However, low calcination temperatures typically coincide with a high content of TiO 2 crystals that remain in the mixed phase. Oakton et al . reported that IrO 2 /TiO 2 materials synthesized by an one‐pot Adams method from NaNO 3 , IrCl 3 ⋅0.6 H 2 O, and TiOSO 4 ⋅0.6 H 2 O at 350 °C retained three different phases, that is, TiO 2 anatase, TiO 2 rutile, and IrO 2 rutile, with IrO 2 nanoparticles (ca.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, titanium dioxide (TiO 2 ) is a stable, commercially available, and inexpensive material , and is frequently used as a catalyst support for Ir , . However, a relatively high amount of Ir or IrO 2 (> 40 wt %) is required to generate sufficient electric conductivity by forming a contiguous network/film of Ir or IrO 2 nanoparticles , , since TiO 2 itself is not conductive. A conductive and stable support material would eliminate the need for a percolating network of Ir or IrO 2 to provide sufficient conductivity across the catalyst layer and, hence, enable lower Ir loadings.…”
Section: Concepts For Ir‐based Oer Catalyst Developmentmentioning
confidence: 99%